Gender and Age Dependent Bacteriological Etiology of Community-Acquired Blood Stream Infection (Bangladesh Journal of Medical Microbiology, 2023)
Background: Bloodstream infection constitutes one of the most serious situations in infectious disease. Objective: The purpose of the presents study was to determine the gender and age dependent etiology of community- acquired urinary blood stream infection. Methodology: This was a retrospective analysis of blood samples from clinically suspected cases of blood stream infection. Samples were collected at Ad-din Women’s Medical College Hospital, Dhaka & Rushmono Specialized Hospital, Dhaka from January 2018 to September 2018. All the samples were collected from inpatient’s and outpatient’s department of our hospital during the study period and processed in Microbiology laboratory. The BD BACTEC FX40 automated blood culture method was used to isolate bacterial pathogens and antimicrobial susceptibility test was performed by Kirby-Bauer disc diffusion method. Results: A total of 483 (16.1%) pathogens were isolated from 3018 bacteremia suspect patient blood specimens. Gram-negative cocci (58.4%) were predominant organisms recovered followed by Gram-positive bacilli (41.6%). Majority of BSI were caused by Gram negative bacteria predominantly Salmonella Typhi (31.1%). Salmonella species was found less prevalent in the children (55%) and more frequent in the age groups 16 to 30 years (85.0%) and more than 60 years (100.0%). Acinetobacter species was found less prevalent in age group 16 to 30 years (7.5%). Escherichia coli was found only few prevalent in the 1 to 15 (0.5%) and higher frequent in the age groups 16 to 30 years (2.5%). Salmonella species isolates appeared to be sensitive to ceftriaxone (91.3%), meropenem (90.7%) and cotrimoxazole (76%). Sensitivity rates of ciprofloxacin, gentamycin and levofloxacin were 87.3% for coagulase-negative Staphylococcus species (CoNS). Conclusion: Both patients’ age and gender are significant factors in determining bloodstream infection.Bangladesh Journal of Medical Microbiology, January 2023;17(1):3-9